FDG-PET/CT Focal Uptake on an Ocular Prosthesis. (June 2018) - Repetto, Alessandra; Igua, Carolina; Sopena, Pablo; Bello, Pilar
Abstract : Abstract: We present a case of an unexpected focally increased radiotracer uptake in an artificial eye in an FDG-PET/CT scan that was performed on a woman with a history of choroidal melanoma. It is crucial to know the type of prosthesis used and the timing of replacement for a correct interpretation of the findings. Recently, an FDG PET/CT was proposed to monitor the vascularity of the prosthesis instead of gadolinium MRI or of 99m Tc bone scintigraphy.